THE GENUS CULLENIA Wight * (Bombacaceae) - KOSTERMANS, A. J. G. H. (Research Center for Biology, 1956)
The monotypic genus Cullenia was established by Wight (Icones PI. Ind. or. 5 (1) : pi. 1761-62 & text, 1851), who differentiated it from Durio Adans. mainly by the lack of a corolla and the position and shape of the anthers.The only species, originally described as Durio ceylanicus by Gardner, was cited by Wight as Cullenia excelsa Wight. K. Schumann corrected the specific epithet rather casually and atributed it (wrongly)to Wight. Bentham (in Benth. & Hook.,Gen. pi. 1: 212. 1867); Baillon (Hist. pi. 4: 159. 1872), Masters (in Hook, f., Fl. Br. Ind. 1: 350. 1874) and Beccari (Malesia 3: 219. 1889) accepted the genus.Bakhuizen van den Brink (in Bull. Jard. bot. Buitenzorg III, 6: 228.1924) incorporated the genus in Durio.In my opinion Cullenia represents a